2014
DOI: 10.4317/jced.51472
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of chamomilla tincture mouthwash on oral aphthae: A Randomized Clinical Trial

Abstract: Introduction: Recurrent aphthous stomatitis (RAS) is a common clinical condition producing painful ulcerations in the oral cavity. However, there has been no optimal therapeutic approach. Topical and systemic steroids commonly prescribed for the condition have local and systemic side-effects. Recently, there is growing tendency toward herbal medication in the modern society. The objective of this study was to assess the efficacy of a chamomilla mouth rinse on reducing the signs and symptoms of aphthous lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 6 publications
(8 reference statements)
1
43
0
4
Order By: Relevance
“…An MTC mouthwash was effective in treating recurrent aphthous stomatitis (12) and oral mucositis (13). In addition, an MTC mouthwash reduced plaque accumulation and gingival inflammation, without significant effects on tooth staining, when used twice a day for 4 weeks (14).…”
Section: Introductionmentioning
confidence: 99%
“…An MTC mouthwash was effective in treating recurrent aphthous stomatitis (12) and oral mucositis (13). In addition, an MTC mouthwash reduced plaque accumulation and gingival inflammation, without significant effects on tooth staining, when used twice a day for 4 weeks (14).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, it may be useful, if not essential, to adopt an alternative therapy. In this scenario, phytotherapy has been adopted as a therapeutic alternative to alleviate symptoms and improve OLP patients’ quality of life; it also offers the advantages of low cost, availability and absence of adverse effects …”
Section: Discussionmentioning
confidence: 99%
“…A variety of approaches have been used to treat oral lichen planus (OLP) including corticosteroids, retinoids, topical cyclosporine, antimicrobials azathioprine, calcineurin inhibitors and surgery .The main disadvantage of these treatments are their secondary effects . Several studies have investigated the application of chamomile for treating different oral diseases, particularly gingivitis, mucositis, aphthous stomatitis, but most were not randomized, controlled trials for the application of chamomile to treat OLP patients . The purpose of this study was to compare the clinical therapeutic efficacy of topical applications of chamomile for treating OLP vs. a placebo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camazulene has a dose‐dependent anti‐inflammatory effect; it inhibits leukotriene B4 synthesis, and the peroxidation of arachidonic acid in neutrophils . Chamomile mouth rinse is prescribed for aphthous lesions, gingivitis, laryngitis, and oral mucositis . It has also been widely used to treat periodontal diseases; Pourabbas et al and Batista et al observed reductions in gingival bleeding as a result of its application.…”
Section: Discussionmentioning
confidence: 99%